Nǣo nayōbāi læ lak patibat nai kānfư̄nfū withī chīwit chāo Karīang (Klum Sœ̄ngsœ̄m Khrư̄akhāi læ Prasān Rātchakān Phūmiphāk, Samnak Bō̜rihān Klāng, Samnakngān Palat Krasūang Watthanatham, Krasūang Watthanatham, 2011)
Preservation of culture and identity of the Karen ethinic minority group in Northern Thailand.